INOVASI PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN SUMATERA TAWALIB PARABEK BUKITTINGGI - Rizki Pebriana (Universitas Muhammadiyah Tapanuli Selatan, 2016)
Kitab kuning learning is judged as difficult and rigid learning and mostly useconventional method like weton, sorogan and halaqah. Actually, kitab kuning learning can be changed to be fun learning. Sumatera Thawalib Parabek Bukittinggi boarding school is an institution that has tried to change the paradigm by making innovation in kitab kuning learning. This research is field research with descriptive qualitative method. In collecting the data, the technique that was used was interview, observation, and documentation study. The result of this research described that there were some innovations that have been done by Sumatera Thawalib Parabek Bukittinggi boarding school. Some among them were, making preparation in form of lesson plan,giving attention to the input quality, and providing tools and supporting fasilities. Besides, kitab kuning learning was served by using variative methods, such as drama, discussion, problem solving and other methods. Kitab kuning learning was also done by utilizing the natural environment as a place to learn, so that kitab kuning learning can be interesting learning by prioritising PAIKEM principle..